PENGARUH DRAMA TRADISIONAL SEBAGAI MOTIVASI PELIHARA DIRI KESEHATAN GIGI DAN MULUT PADA ANAK - Sukini Sukini; Yodong Yodong; Sariyem Sariyem (Jurnal Kesehatan Gigi, 2017)
TITLEThe influence of traditional drama as the motivation of self-care of oral and dental health in childrenABSTRACTThe caries rate among primary school-aged children is still high. Based on Riskesdas (Riset Kesehatan Dasar / Base Health Research) in 2013, children with ages from 10-14 years old with dental and mouth health problems reach 25,2%. It takes a genuine and concerted effort from all parties to promote oral hygiene at the age of the children, such as by growing a self-maintained motivation. This study aims to generate a motivation in children with cultural arts approach based on local wisdom, the art of traditional drama.This research is descriptive, which is a research method that was conducted with the aim to create a picture or description of the problem in the case of motivation self-care subjectively. This motivational factor will be assessed using the “Yes-No” questionnaire. For positive questions, each “Yes” answer will be given a “5” score and the “No” answer will be given “0” score. The opposite, for negative questions, each “Yes” answer will be given a “0” score and the “No” answer will be given a “5” score. The population is 72 children grade 3,4, and 5.The result of the research showed that the motivation after being treated with traditional drama was a significant change with an average of 85.69. The number is much higher when compared with the motivation before treatment is given with an average of 48.47. Traditional drama intervention can be used as an alternative media for health education implementation because based on the results of the above research can improve the motivation change. Keywords : Traditional drama, motivation self-preservation